Guidance-Based Path Following of an Underactuated Ship Based on Event-Triggered Sliding Mode Control - Yuxi Zhang; Yong Liu (Journal of Marine Science and Engineering, 2022)
In this paper, the path following of an underactuated ship as a fundamental application for autonomous sailing in seaways is studied. First, the guidance system based on the line of sight (LOS) method is established to handle underactuated dynamics of ship motion. Then, path following control is converted to heading control with fewer dimensions. Second, the extended state observer (ESO) is used to observe unknown dynamics of ship motion. Third, the sliding mode control method is highly robust to external disturbance and is employed to design the controller. Fourth, the event-triggered mechanism (ETM) is included to reduce the trigger time. All the closed-loop signals are shown to be bounded by the Lyapunov theory. Simulations are carried out to verify the effectiveness of the proposed method.